Do Indonesia Tax Rules Support Or Hinder Sme’s Tax Conformity? - Bagas Deny Reza; Karel Marcellino; Ulfi Dania; Ahmad Syifaudin (Journal of Social Research, 2024)
This study aims to determine the effect of tax knowledge, tax awareness, and tax sanctions on tax compliance in the SME sector in Cirebon City, Indonesia. The population of this study was 2,426 SMEs in Cirebon City, and a sample of 343 was used for analysis, with purposive random sampling employed. This study employs a quantitative approach with SPSS. For testing the analyses employed, this study utilizes a quantitative approach. The findings indicate that tax compliance is significantly influenced by tax knowledge, tax awareness, and tax enforcement among SME actors.